Dėl lietuvių dvikamienių asmenvardžių kamieno dal- atsiradimo - Sinkevičiūtė, Daiva (Baltistica, 2010)
ON THE ORIGIN OF LITHUANIAN COMPOUND PROPER NAMES WITH FIRST STEM dal- Lithuanian compound proper names with first element dal- (as well as place names derived from them) cannot contain an independent element dal- related to the word family of Lith. dal-ià, dal-ýti. Lithuanian onyms with first element dal- originated in two different ways: a) cases with second element ‑mant- arising through contamination of the originally unrelated proper names Daũmantas and Dálmatas; b) cases with second element ‑ged‑arising through folk etymology alteration of dau‑ged- as dalg-ed- (vel sim.). There are no other proper names with dal- that could be related to the root dal-. In some cases proper nouns with dal- can be incorrect renderings of dau- before [g] due to Slavic influence or, alternatively, they may be an irregular variant of dol- (for dau-). Lithuanian compound proper nouns with dal- are thus all secondary, having arisen through alteration of already existing proper nouns. The evidence of the other Baltic languages is entirely unclear. A thorough analysis of the writing tradition of Curonian personal names would be needed in order to test the possibility that Cur. Dalbutt contains the first element dal- to be related to Lith. dal-.